2010
DOI: 10.1111/j.1743-6109.2010.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors, Condom Use, and Sexual Health of Americans Over 50: Implications for Sexual Health Promotion for Older Adults

Abstract: Introduction In the contemporary U.S., men and women are living longer and healthier lives. As such, many people spend greater portions of their lives as sexually active individuals. Yet, little is known about the myriad of ways that older adults experience their sexual lives. Aim This study sought to assess the context and frequency of sexual behaviors, condom use, sexual pleasure, and sexual experience of men and women over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
200
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(234 citation statements)
references
References 33 publications
24
200
2
8
Order By: Relevance
“…an average decline in new sexual exposures with increasing age, as has been reported previously (54). It seems unlikely that the relatively higher HPV incidence in older seropositive versus younger seropositive women reflects a uniquely high sexual risk among the older seropositives.…”
Section: Figuresupporting
confidence: 66%
See 1 more Smart Citation
“…an average decline in new sexual exposures with increasing age, as has been reported previously (54). It seems unlikely that the relatively higher HPV incidence in older seropositive versus younger seropositive women reflects a uniquely high sexual risk among the older seropositives.…”
Section: Figuresupporting
confidence: 66%
“…The benefit of vaccination in a sexually active woman is uncertain (20), and on a population level, HPV vaccination with increasing time since sexual debut (correlated with aging) rapidly loses cost-effectiveness (73). This loss of costeffectiveness is driven by a combination of reduced frequency of new sexual exposures with age and the lack of efficacy of vaccine in women already infected with vaccine-associated HPV types (54,74,75). The argument that on an individual level nearly all women will benefit from HPV vaccination, since less than 1% of women have evidence of prior infection to all four vaccine types, is overly simplistic (76).…”
Section: Implications Of the Proposed Model Of Hpv Latencymentioning
confidence: 99%
“…32 Although this is not unique to older people, relationship transitions -common in older age -may increase the likelihood of meeting new partners after an established relationship. 33 Studies indicate condom use among older people is low, 34 which may be due to a lack of confidence in negotiating condom use when starting a new relationship, or because postmenopausal women no longer worry about pregnancy. 28 Additionally, availability of drugs such as sildenafil mean erectile dysfunction may no longer be a barrier to sex for older men.…”
Section: Discussionmentioning
confidence: 99%
“…(3) In the context of sexuality, researchers have demonstrated that the elderly continue to be sexually active, even after 80 years of age. (4) A study conducted in northeastern Brazil also demonstrated that in this country, many elderly people maintain an active sex life with desires and pleasures and often continue to have sex in an unsafe manner. (5) This may be because the elderly do not perceive themselves as vulnerable to sexually transmitted infections (STIs) and HIV/AIDS, (6) a perception that can be contested by global data on the distribution of these diseases by age group.…”
Section: Introductionmentioning
confidence: 99%